Extent and socio-economic significance of slope-instability on the Island of Hispaniola (Haiti and Dominican Republic) - Mora C., Sergio (1995)
On the island of Hispaniola, unstable slopes are common phenomena, especially those associated with intensive soil erosion and landslides. In Haiti, soil erosion is extreme and has contributed to the problems of food supply and environmental degradation that currently afflict this country. Landslides are also common, such as those around the Peligre reservoir and the Massif de la Selle. In the Dominican Republic, intensive soil erosion is severe, as is the case of the neighborhood of Banica, where land utilization is completely gone. Large landslides are widespread throughout Septentrional and Central Mountain Ranges, examples of which are the well known case at the town of Carlos Díaz in the Septentrional Range and the many slides generated in the Central Range during the passage of the David and Frederic tropical storms in 1979. Climatic and geomorphic conditions have contributed to these phenomena, which in many cases are triggered by the frequent transit of hurricanes and by earthquakes. Irrational human activity, however, is steadily aggravating the situation.